Pengaruh Kompetensi, Disiplin Dan Pengembangan Karier Terhadap Kinerja Karyawan PT. Asam Jawa Medan - Swandy L. Sihombing; Eni Melina Nainggolan; Dikki Diafri; Grace Desyantika Sitompul; Muhammad Agung Anggoro (Mahesa Research Center, 2020)
PT. Asam Jawa is a company operating in the oil palm sector as an object that we make to conduct research. Research or research is carried out to evaluate and test whether there is an influence or impact of competence, discipline, and career development on employee performance at PT. Asam Jawa, the city of Medan. Where the multiple Linear Regression analysis method that researchers use in this study, this method is a linear regression model that involves more than one independent variable or hypothesis. With the population taken, namely all employees, the number is 45 employees. And testing the sample of researchers in the study is to use saturated sampling where all employees of PT. Asam Jawa, Medan, which used as a sample of 45 respondents and 30 respondents as a test of validity and reliability of PT. Perkebunan Nusantara III. From the results of researchers in the study stated that competence, discipline, and career development simultaneously (simultaneously) and partially (independently) are significant and have a positive effect on the performance of company employees, where the coefficient of determination is 0.609 which proves that (x1) competence, ( x2) discipline and (x3) career development have an effect on or have a relationship with employee performance with the percentage quality of 60.9% and the remaining 39.1% are the results of hypotheses or foreign / different variables not examined by researchers in the study.